Konfixes with postpositive component –ок in the history of Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article is dedicated to the ways of formation of structure and development of confixal derivatives with affixes су-…-ок, з(с)-…-ок, пере-…-ок, перед-…-ок, роз-…-ок, уз-…-ок, у-…-ок, через-…-ок in the course of writing period of the Ukrainian language development.
Keywords: konfix; confixal derivative; confixal way of word-building